UI/UX DESIGN OF BPMP INFRASTRUCTURE RENTAL USING GOAL DIRECTED DESIGN METHOD - Alfredo, Boby; I. Inan, Dedi; Juita, Ratna; Sanglise, Marlinda; Y. Baisa, Lorna (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Technological advancements have transformed human life paradigms, including in the provision of facility rental services by the Educational Quality Assurance Agency (BPMP) of West Papua. This research aims to design the user interface (UI/UX) of the BPMP West Papua facility rental application to provide a satisfying user experience through clear information, easy navigation, and appealing visual design. The method used in designing the UI/UX of this application is Goal Directed Design (GDD), which follows six stages of research which include Research, Modeling, Requirements, Framework, Refinement, and Support. Evaluation results using the System Usability Scale (SUS) with 20 respondents indicated that the application achieved an average SUS score of 77.8 (Grade B), demonstrating good acceptance of the application prototype. These evaluation results confirm that the prototype is acceptable.